DIETARY DIVERSITY AND SELECTED MICRONUTRIENTS STATUS OF PRIMARY SCHOOL PUPILS IN MAKURDI LOCAL GOVERNMENT AREA OF BENUE STATE - Tsa, Erdoo M.; Iombor, Theophilus T.; Okonkwo, Lovina E. (FUDMA Journal of Sciences, 2025)
Dietary diversity is influenced by accessibility to food, the more food groups included in a daily diet, the greater the likelihood of meeting nutrient requirements. Hence, the study was conducted to investigate the association between dietary diversity scores (DDS) and the nutritional status of 388 preschool children in Makurdi, Benue state, Nigeria. A 24 hour dietary recall questionnaires and dietary diversity scores (DDS) were calculated based on 7 food groups (starchy staples, leafy vegetables, Vitamin A rich fruits and vegetables, other fruits and vegetables, meat and fish, eggs, legumes and seeds/nuts, milk and milk products). The results revealed cereals and cereal products (51.0%) are mostly consumed daily, followed by roots and tubers (19.5%). The consumption of fruits and vegetables was low with 6.3% of the pupils consuming fruits daily and 10.9% consuming vegetables daily. This highlights potential gaps in the consumption of essential food groups contributing to dietary diversity, hence, this study reinforce the importance of continued nutrition education of mothers, caregivers and preschool staff on the need to ensure consumption of diverse food sources in order to improve the nutritional status of children. Further studies are recommended on factors associated with low dietary diversity among preschool children.